2009
DOI: 10.3233/ppl-2009-0208
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Ethics Committees in Europe on issues related to clinical trials in paediatrics: Results of a survey

Abstract: The rights and well-being of children involved in clinical research in Europe should be assured by the respect of ethical considerations and legal rules. Specific provisions are included in the Directive 2001/20/EC (CT-Dir) aimed at providing a homogeneous ethical and legal context to perform clinical trials in Europe.The TEDDY Network of Excellence carried out a "Survey on the ethical and legal frameworks existing in Europe for paediatric clinical trials" to examine the measures enforced by Member States to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…An inventory was carried out to identify Ethics Committees operating in Europe. The results of the first TEDDY survey (10,11) provided the approximate number of ECs and the website addresses where their contact details are available. Other sources were TEDDY and RESPECT Partners, MS Medicines Agencies and personal direct information.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An inventory was carried out to identify Ethics Committees operating in Europe. The results of the first TEDDY survey (10,11) provided the approximate number of ECs and the website addresses where their contact details are available. Other sources were TEDDY and RESPECT Partners, MS Medicines Agencies and personal direct information.…”
Section: Methodsmentioning
confidence: 99%
“…• Networking may be an essential tool to be used to enhance the role of ethics committees in supporting paediatric research. Results showed that many differences exist in the protection of minors involved in clinical trials across Europe mainly because of the Directive implementation process and a lack of coordination among MS (10,11).…”
Section: Key Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, following the approval of the Paediatric Regulation, destined to increase the number of paediatric trials, the art. 4 of Directive 2001/20/EC was considered insufficient to protect children involved in a trial [12]. The 'Ethical Recommendations on paediatric trials' issued in 2008 by the EU Commission [13], represent the more advanced regulatory framework for paediatric research in Europe.…”
Section: The Current Regulatory Framework For Approving Clinical Trialsmentioning
confidence: 99%
“…Another example of criticism in paediatric drugs availability deals with rare diseases: both in EU and in the U.S, very few medicinal products for rare diseases affecting children have a paediatric indication 12 . As a consequence, in the U.S. (but not in EU), specific orphan programs for paediatrics have been recently proposed (Rare Pediatric Disease Priority Review Voucher Program).…”
mentioning
confidence: 99%